Thrombosis: A Function of Surface Charge and/or Chemistry of Collagen - Sawyer, P.; Stanczewskl, B.; Stillman, R.; Kirschenbaum, D.; Sivakoff, S.; Lucas, T. (Thrombosis and Haemostasis, 1977)
Examination of porcine prosthesis and bovine heterografts using histologic, SEM and physical examination revealed that ; (1) they have a measurable half life in terms of function; (2) the areas of failure are predictable; (3) the structure of the observed thrombus is unusual.A number of collagen and human umbilical cord prostheses were prepared by bonding a variety of aliphatic acids to the helical polypetide collagen side chains to produce a repeating surface chemistry. The control (fresh or ficin digested collagen) was compared to (i) glutaraldehyde tanned (GT)(-) charged, (ii) GT plus (+) charged and (iii) GT neutral surface. These resulting tubular grafts were implanted in dog carotid and femoral arteries.The results indicate the most important factor in long term patency and function is a coval-ently bonded, GT (-) surface.Histologic examination reveals that manipulation of the surface charge of collagen results in bizarre thrombus formation with aggregation of a singie cell type or protein element.The (-) charged grafts were free from thrombus. Control collagen grafts contained classical fibrinogen and cellular thrombus. The (+) charged grafts had a pseudo-thrombus i.e. increased fibrinogen fragments (& B) monomers plus trapped cell deposition. The neutral grafts had a less dense, branched fibrinogen deposit with some celluiar elements.In summary, the structural, chemical and surface charge configuration of collagen can be manipulated to produce a biological cardiovascular prosthesis with improved performance.